Cairo City guide CCG - Zhoraya Productions; AR Habibi Film ([Egypt] : Ar Habibi Film, 2002)
An overview of Egypt, which focus on Cairo that discesses the country's, geography, history, economy people and culture
Editor, H. Onni Nonorial; graphic design, H. Masykur Abdullah; cameraman, H. Murry darmoko; executive producer, Hj. Dra Rina Siswani
Keywords: Egypt -- Cairo; Egypt -- History